Climate change effects on submarine groundwater discharge and regional variations along the Korean Peninsula - Hahn Chul Jung; Yeosang Yoon (Communications Earth & Environment)
Abstract Climate change impacts fresh submarine groundwater discharge on the Korean Peninsula, increasing the vulnerability of coastal regions to environmental degradation and economic consequences. Here, we provide regional estimates of fresh submarine groundwater discharge along the entire coast using established water balance methods. Our findings reveal that the western and southern coasts of the southern Korean Peninsula exhibit higher fresh submarine groundwater discharge rates due to greater net precipitation compared to the northern Korean Peninsula. Differences in drainage length between the east and west coasts, along with substantial tidal flats, significantly influence submarine groundwater discharge rates. Climate change drives variations in fresh submarine groundwater discharge, with rising trends in the southern Korean Peninsula during spring and winter, while the northern coastal watersheds show consistent increases across all seasons. Coastal vulnerability to offshore contamination from land use development affects 15% of the coastline. Notably, between 1990 and 2020, the risk in the southern Korean Peninsula’s coastal catchments increased by 38%. Our analysis also highlights heightened vulnerability to saltwater intrusion in the southwestern Korean Peninsula.